Od romanov do teoloških esejev: pregled slovenskih prevodov poljske literature v letu 2017 - Unuk, Jana (Przekłady Literatur Słowiańskich, 2019)
The article deals with translation choices by Slovene translators from Polish literature in 2017, on the presumption that both literatures, that of source and that of the target language, perceive each other as peripheral in terms of Even-Zohar’s theory of literary polysystems. Nevertheless, as much as 14 Polish books of different genres were translated into Slovene language in 2017, among them novels, poetry, a play, and theological essays.